Rencana Aksi Perubahan Terhadap Organisasi - Jusmawati Jusmawati; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
Humans naturally become part of various social groups throughout their lives, from family to broader communities. An organization is a structured group that organizes the roles and responsibilities of its members to achieve common goals. Organizational change is an important and complex process affecting various aspects such as structure, culture, technology, and human resources, driven by both internal and external factors. The change process includes stages from identifying needs to institutionalizing changes as part of the organizational culture. The success of change is highly influenced by leadership, effective communication, managing resistance, as well as employee training and development. A thorough understanding of change dynamics and the central role of leadership is crucial to ensure successful implementation of change and the sustainable achievement of organizational objectives.